Lifestyle As Causes of Sexual Deviance In Islamic Perspective: English - Salma Nuha Ghufron; Muhamad Arifin (STAI Terpadu Yogyakarta, 2023)
Implementing a lifestyle in accordance with Shari’ah has a close correlation with the formation of a noble character and positive mindset in humans to avoid all forms of ugliness and deviation. The concept of the Islamic lifestyle also supports the preservation of human life, protects future generations, and maintains the integrity of humanity. This research uses qualitative methods with case studies to research natural object conditions, where the researcher is the key instrument, and is carried out through interviews and observations. The research informants were community groups with deviant sexual orientation in Bandung and medical experts in the world of psychology. The results showed a correlation between lifestyles that have an impact on sexual deviance, namely, the widespread spread of sexual deviance: LGBT, especially gays in Bandung since 2016, as a result of the consumption of haram food and drinks, as well as dressing and behaving in ways that violate the guidance of Islamic law. This study aimed to analyze the correlation between lifestyle and the phenomenon of sexual deviance: LGBT in Bandung, as well as the Islamic view of the correlation between the two.